Lifestyle Habits and Cardiovascular Risk Factors in a Young Population - Medeiros, A.M. (2012)
Although CVD is mostly present in adult life, atherosclerosis starts in childhood. Health promotion and cardiovascular prevention strategies can generate health gains and, if implemented in childhood, those gains will be superior. In pathologies with multifactorial etiology like CVD, the preventive approach should be addressed to risk factors, specially the modifiable related to unhealthy lifestyle habits. The aims of this work are: to characterize the lifestyle habits and determine the cardiovascular risk factors of a young population, and to co-relate these factors.